TEOLOGI INKLUSIF NURCHOLISH MADJID (PEMIKIRAN TENTANG PLURALISME DAN LIBERALISME AGAMA) - Suryadi Suryadi (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2017)
Abstract: Inclusive Theology Nurcholish Madjid (Thought About Religious Pluralism and Liberalism). Interpret the keyword Allah be ‘God’ is conflicting concepts. The question is whether the concept of God that is understood by other religions is the same as the concept of God in Islam? God in Islam, for example, childless and not begotten, whereas the God of the Christian son. God in Islam is only a temporary one God in Hinduism there are three, namely Brahma, Vishnu and Shiva, and each has a different role. If indeed God in Christians, Zoroastrians and others are the same, why the Prophet invited them to Islam or to invite them to the sentence sawa‘? Kalima sawa ‘is not a theological compromise, not a common platform, but monotheism in Islam which became the teachings of previous Prophets. Point of similarity is not just believe in God, but the concept of the oneness of God brought earlier prophets and include Islam. The formulation of the problem in this research: How Nurcholish Madjid Thoughts on Religious Pluralism? And How Nurcholish Madjid Thinking about Religion Liberalism? Kind of research is a library (library research). The results of this study concluded that the views Nurcholish Madjid, basically pluralistic society or the nature of pluralism, it is not enough just with the attitude acknowledge and accept the fact that the society is pluralistic, but—more fundamentally—must be accompanied by a sincere attitude to accept pluralism as a positive value and the grace of God to man, for it would enrich the cultural growth through dynamic interaction and cross-cultural diversity. Pluralism should also not be understood merely as a “goodness negative” (negative good), just judging from its usefulness to get rid of fanaticism (to keep fanaticism at bay). Pluralism should be understood as “a true affinity diversity in the bonds of civility” (genuine engagement of diversities within the bonds of civility). In fact, pluralism is a necessity for the survival of humanity, among others, through the mechanism of checks and balances that result. The process of liberalization and secularisation which later evolved into isms in view of Cak Nur are efforts to break away from traditional values. The consequences of this attitude is the emergence of the notion of “personal religious Nodes: piety, resignation, sincere”. Because he let go of traditional values, the exposition does not contain a new and fresh theory that can be useful as a remedy for the psychological plight of modern man.